2012
DOI: 10.1371/journal.pone.0046151
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Signaling Modulates Cell Survival in Experimental Ischemic Stroke Penumbra and Initiates Long-Term Repair in Young and Aged Rats

Abstract: BackgroundDocosahexaenoic acid, a major omega-3 essential fatty acid family member, improves behavioral deficit and reduces infarct volume and edema after experimental focal cerebral ischemia. We hypothesize that DHA elicits neuroprotection by inducing AKT/p70S6K phosphorylation, which in turn leads to cell survival and protects against ischemic stroke in young and aged rats.Methods and ResultsRats underwent 2 h of middle cerebral artery occlusion (MCAo). DHA, neuroprotectin D1 (NPD1) or vehicle (saline) was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 35 publications
2
49
0
Order By: Relevance
“…In line with the latter view, n-3 PUFAs are thought to confer protection against cerebral ischemia through multiple mechanisms. In addition to the acute effects, such as the attenuation of oxidative stress (Bazan, 2005), anti-inflammatory effects (Zhang et al, 2010), induction of heme oxygenase 1 (Zhang et al, 2014), and pro-survival functions (Eady et al, 2012), we recently reported potent neurorestorative properties of n-3 PUFAs, such as the promotion of endogenous neurogenesis and oligodendrogenesis (Hu et al, 2013). Transgenic overexpression of n-3 PUFAs significantly increased neural stem cell proliferation and differentiation, and increased neuroblast migration to the injury site (Hu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In line with the latter view, n-3 PUFAs are thought to confer protection against cerebral ischemia through multiple mechanisms. In addition to the acute effects, such as the attenuation of oxidative stress (Bazan, 2005), anti-inflammatory effects (Zhang et al, 2010), induction of heme oxygenase 1 (Zhang et al, 2014), and pro-survival functions (Eady et al, 2012), we recently reported potent neurorestorative properties of n-3 PUFAs, such as the promotion of endogenous neurogenesis and oligodendrogenesis (Hu et al, 2013). Transgenic overexpression of n-3 PUFAs significantly increased neural stem cell proliferation and differentiation, and increased neuroblast migration to the injury site (Hu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The defi ciency in -3 PUFAs is considered to be a risk factor for human mental and neurological disorders ( 13,31,32 ). Exogenous application of -3 PUFAs slowed the progression of Alzheimer's disease in mice ( 33,34 ), prevented Huntington's disease ( 35 ), showed therapeutic potential for spinal cord injury (36)(37)(38)(39), and improved neurological and histological outcomes in the focal cerebral ischemia model ( 5,(40)(41)(42). However, these beneficial effects of -3 PUFAs are not consistently detected ( 13,43 ).…”
Section: Attenuated Microglia Activation and Astrocytes Reaction In Tmentioning
confidence: 99%
“…Furthermore, blood analysis (White et al , 2006) showed that, although 3 hours after resuscitation arterial neuroprotectin D1 (NPD1) increased in all animals, it was three times higher in hypothermic animals. Unlike NSE and S-100B, which are markers of injury (Calderon et al , 2014), NPD1 is an endogenous lipid mediator that reduces inflammation and apoptosis in neurons undergoing oxidative stress (Eady et al , 2012). These findings suggest that cooling beyond the 3-hour postresuscitation window may miss an important mechanism of neuroprotection.…”
Section: Introductionmentioning
confidence: 99%